2016
DOI: 10.3389/fpls.2016.00196
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Enhances Water Stress Tolerance by Improving Root Hydraulic Conductance in Solanum lycopersicum L.

Abstract: Silicon (Si) can improve drought tolerance in plants, but the mechanism is still not fully understood. Previous research has been concentrating on Si’s role in leaf water maintenance in Si accumulators, while little information is available on its role in water uptake and in less Si-accumulating plants. Here, we investigated the effects of Si on root water uptake and its role in decreasing oxidative damage in relation to root hydraulic conductance in tomato (Solanum lycopersicum ‘Zhongza No.9’) under water str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
155
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(179 citation statements)
references
References 54 publications
21
155
1
2
Order By: Relevance
“…As for the use of biostimulant to contrast abiotic stresses, Goñi et al [8] and Di Stasio et al [9] recently reported the use of seaweed extracts from Ascophyllum nodosum to enhance the tolerance of tomato plants to drought and salinity stress, respectively. This positive effect was observed also with other biostimulants, such as protein hydrolysate on lettuce [10], chitosan on white clover [11], and silicon on tomato [12]. Regarding the stress caused by nutrient deficiency, biostimulants can contribute to soil nutrient availability, uptake, and assimilation of nutrients to the plants [13].…”
Section: Introductionmentioning
confidence: 74%
“…As for the use of biostimulant to contrast abiotic stresses, Goñi et al [8] and Di Stasio et al [9] recently reported the use of seaweed extracts from Ascophyllum nodosum to enhance the tolerance of tomato plants to drought and salinity stress, respectively. This positive effect was observed also with other biostimulants, such as protein hydrolysate on lettuce [10], chitosan on white clover [11], and silicon on tomato [12]. Regarding the stress caused by nutrient deficiency, biostimulants can contribute to soil nutrient availability, uptake, and assimilation of nutrients to the plants [13].…”
Section: Introductionmentioning
confidence: 74%
“…Ma et al (2016) also suggested that Si supplement wheat plant showed lower lipid peroxidation, glutathione and total flavonoid content whereas increased ascorbate content was observed. Similarly, Shi et al (2014, 2016) reported that Si supplementation in tomato plants under PEG induced drought stress caused tolerance via increased SOD and CAT activities as well as improved water uptake ability of roots (Table 1). Whilst, Gunes et al (2008) observed that Si decreased MDA and APX activities in sunflower during drought condition (Table 1).…”
Section: Drought Stressmentioning
confidence: 86%
“…Therefore, tomato may be an ideal plant to study the exact physiological and biochemical mechanism for siliconmediated tolerance to drought stress. In our previous study, we observed that exogenous silicon could increase water stress tolerance by enhancing root hydraulic conductance and decreasing oxidative damage in tomato seedlings (Shi et al 2016), suggesting the involvement of silicon in physiological and biochemical processes. However, the mechanism for silicon-mediated water stress tolerance in tomato still needs to be explored.…”
Section: Introductionmentioning
confidence: 92%